2020
DOI: 10.3390/met10020204
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the DOS by DL−EPR of UNSM Processed Inconel 718

Abstract: In this work, influence of ultrasonic nanocrystal surface modification (UNSM) on the degree of sensitization (DOS) in Inconel 718 has been studied and correlated with the resulting microstructure. The UNSM processed samples decreased their grain size from 11.9 µm to 7.75 µm, increasing the surface of grain boundaries, and thus enhancing the area where δ phase and niobium carbides precipitate. The effect of the UNSM process on the DOS of Inconel 718 was studied by the double loop electrochemical potentiokinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Corrosion properties by surface modification have recently been studied as follows: Shot peening on the corrosion of aluminum alloy [ 19 , 20 ] and the corrosion properties of stainless steel [ 21 , 22 ]; laser peening on the corrosion of Alloy 600 [ 23 ], the corrosion of 304 stainless steel [ 24 ], the corrosion of stainless steels [ 25 , 26 , 27 , 28 , 29 ], the corrosion of aluminum alloy [ 30 ], and the corrosion of magnesium alloy [ 31 ]; UNSM on the corrosion of nickel base alloys [ 32 , 33 , 34 ] and the corrosion of stainless steels [ 35 , 36 , 37 , 38 ]; and comparison between laser peening, shot peening, and ultrasonic peening [ 8 ]. Most recent research efforts on surface modification methods have shown beneficial effects on the corrosion of various alloys [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. In some cases, detrimental effects of surface modification methods can be induced.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion properties by surface modification have recently been studied as follows: Shot peening on the corrosion of aluminum alloy [ 19 , 20 ] and the corrosion properties of stainless steel [ 21 , 22 ]; laser peening on the corrosion of Alloy 600 [ 23 ], the corrosion of 304 stainless steel [ 24 ], the corrosion of stainless steels [ 25 , 26 , 27 , 28 , 29 ], the corrosion of aluminum alloy [ 30 ], and the corrosion of magnesium alloy [ 31 ]; UNSM on the corrosion of nickel base alloys [ 32 , 33 , 34 ] and the corrosion of stainless steels [ 35 , 36 , 37 , 38 ]; and comparison between laser peening, shot peening, and ultrasonic peening [ 8 ]. Most recent research efforts on surface modification methods have shown beneficial effects on the corrosion of various alloys [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. In some cases, detrimental effects of surface modification methods can be induced.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The UNS N07718 alloy is corrosion-resistive in oil elds, such as fasteners, bolts, and nuts, where a shallow sour (sweet) condition is associated with the localised corrosion. 5,6 The sweet wells are mildly corrosive to Ni-based alloys due to the passive lm on the alloy surfaces, which governs the localised corrosion resistance during service in the environments. For these reasons, the precipitation-hardened UNS N07718 alloy provides the desired mechanical properties 7,8 and localised corrosion resistance in sour environments.…”
Section: Introductionmentioning
confidence: 99%
“…The UNSM promoted a high twin and dislocation density region on Inconel 718, preventing the fatigue crack to nucleate by creating barriers for the dislocation to move forward, delaying the failure of the samples [16]. Concerning the corrosion performance, the UNSM treatment has also positively influenced the corrosion behavior; among the techniques used to test it, electrochemical impedance spectroscopy (EIS) is one of the most common [12,17,18]. The combination of UNSM and nitriding enhanced the impedance by five times compared to the control sample, improving the pitting corrosion protection [19].…”
Section: Introductionmentioning
confidence: 99%